The relationship between self-determination and burnout: Mental health outcomes in medical residents. - Hassan Mobarak; Chadia Haddad; Pascale Salameh; Evelyne Towair; Myriam El Khoury-Malhame; Rajaa Chatila (PLoS ONE)
Background Burnout is a pervasively increasing threat to personal and professional wellbeing and performance. It is yet understudied in relation to basic psychological needs (BPN), especially in at-risk population such as medical residents. This study intends to explore the differential relationship between various aspects of burnout including depersonalization (DP), emotional exhaustion (EE) and lack of personal achievement (PA) and subsets of BPN satisfaction or frustration namely autonomy, relatedness, and competence, with the framework of the Self-Determination Theory (SDT) in healthcare. Materials A total of 110 medical residents in various Lebanese hospitals were included. Demographics and standardized scales were used to measure basic psychological need satisfaction and frustration (BPNSFS), burnout (MBI), depression and anxiety (PHQ-4). Residents were also asked about subjective evaluation of academic training and level of impact by ongoing crises (COVID-19 pandemic, Beirut port explosion and financial breakdown). Results Result point to alarming prevalence of burnout and mental distress in our sample. It also indicates a differential correlation between gender, financial security and various subsets of burnout. It lastly points to association of DP with overall satisfaction scale (Beta = 0.342, p = 0.001) and PHQ-4 scores (Beta = -0.234, p = 0.017), while feeling burdened to attend lectures and having been physically affected by the Beirut blast correlated with a sense of PA (Beta = 0.332, p = 0.010, Beta = 0.187, p = 0.041 respectively) and PHQ-4 (Beta = 0.341, p = 0.000), interacting with COVID-19 patients (Beta = 0.168, p = 0.020) and feeling protected in the working environment (Beta = -.231, p = 0.002) showed a significant association with EE. Discussion Within the SDT framework, this study highlights the complex interplay between collective crises, subjective evaluations or work conditions and other demographics with aspects of burnout in medical residents. It mostly points to the need address this at an individual but also an institutional level to buffer distress in future healthcare providers.